Tantangan dan Peluang Manajemen Masjid di Era Digital - Tri Tami, Novi; Handayani, Fitri; Firtanosa, Aan (Institut Agama Islam Negeri Kerinci, 2024)
Mosques are not only used for ritual worship such as congregational prayers, dhikr, reciting the Koran, prayer and praying, but play an important role in changing values ​​through the habluminannas method by including the physical support of the group of houses of worship, which is of concern, including contribution, charity, donation, fitrah, and tolerance as volunteering and lending a hand or helping others is the center of civilization. The research method used is a qualitative descriptive program. Management of mosque funds can now be designed to be more efficient and productive, such as managing contributions, online payments, and more transparent and accurate financial records, which helps mosques improve the function of mosque welfare boards. In operation, the information system can be used to organize mosque activity programs, register congregations for special events, and monitor activity applications. Mosque administrators have been successful in dealing with digital media and taking advantage of technological advances to improve services to the congregation through social media, handling information regarding funds, online contributions, management activity calendars, etc.